Comparative characteristics of older people with type 1 diabetes treated with continuous subcutaneous insulin infusion or insulin injection therapy: data from the German/Austrian DPV registry. Issue 5 (15th January 2020) - Grammes, J.; Küstner, E.; Dapp, A.; Hummel, M.; Kämmer, J.‐C.; Kubiak, T.; Schütz‐Fuhrmann, I.; Zimny, S.; Bollow, E.; Holl, R.W.; ,
Abstract: Aim: To compare clinical characteristics and outcomes in adults with type 1 diabetes aged ≥ 60 years using continuous subcutaneous insulin infusion (CSII) vs. insulin injection therapy. Further, to determine the percentage of older adults with type 1 diabetes using CSII. Research design and methods: Retrospective study using data of the Diabetes Prospective Follow‐up Registry (DPV). Including percentage CSII use from 2008 to 2018, and the characteristics of 9547 individuals extracted from the DPV in March 2019 ( N = 1404 CSII; N = 8143 insulin injection therapy). Wilcoxon rank sum tests were used for continuous variables and chi‐square tests for categorical variables to compare clinical characteristics of people using CSII vs. insulin injection therapy. Adjusted analyses used generalized linear models to compare diabetes‐related outcomes. Results: CSII usage has increased in older adults (from 12% in 2008 to 23% in 2018). After adjustment, CSII was associated with lower HbA1c [60.7 mmol/mol (7.7 ± 0.1%) vs. 62.8% (7.9 ± 0.1%)], lower daily insulin dose (0.49 ± 0.02 vs. 0.61 ± 0.01 IU/kg), fewer days in hospital (8.1 ± 0.12 vs. 11.2 ± 0.11 days/person‐year), fewer severe hypoglycaemic events (0.16 ± 0.02 vs. 0.21 ± 0.03 events/person‐year) and fewer diabetic ketoacidosis (0.06 ± 0.01 vs. 0.08 ± 0.01 events/person‐year). Individuals on CSII showed lower rates of microalbuminuria and also have a diagnosis of depression and neuropathy. Conclusions: A growing number of older adults are using insulin pumps. Older age in itself should not be seen as a contraindication for CSII. What's new?: Diabetes technologies have to be individually tailored to the needs, wishes, clinical characteristics and capabilities of users. Research on older people with type 1 diabetes using continuous subcutaneous insulin infusion CSII is scarce. CSII usage has increased in adults aged ≥ 60 years. People using CSII report slightly better glycaemic control and fewer acute diabetes complications. CSII usage in older people with type 1 diabetes is a topic of increasing importance. More emphasis should be put on the needs and wishes of this specific age group. Older age in itself should not be seen as a contraindication for CSII.